Emotional adjustment post-stroke: A qualitative study of an online stroke community. Issue 3 (16th March 2021) - Smith, F. E.; Jones, C.; Gracey, F.; Mullis, R.; Coulson, N. S.; De Simoni, A.
ABSTRACT: Understanding of emotional adjustment after stroke is limited. Under one-third of stroke survivors reporting emotional problems receive support. The aim of this study was to explore the process of emotional adjustment post-stroke and investigate the role played by participation in an online stroke community. We applied thematic analysis to 124 relevant posts within 114 discussion threads, written by 39 survivors and 29 carers. The contribution of online community engagement to emotional adjustment was explored using the Social Support Behaviour Code. Stroke survivors share common experiences of emotional adjustment and may not necessarily reach complete acceptance. Positive and negative trajectories of emotional adjustment were identified. Survivors progressed along, or moved between, positive and negative pathways not in a time-dependent manner but in response to "trigger events, " such as physical setbacks or anti-depressant treatment, which may occur at any chronological time. An adapted version of Suhr's 1990 Social Support Behaviour Code showed that support provided through the online community took many forms, including advice, teaching, empathy and normalization of concerns. Participation in the stroke community was itself deemed to be a positive "trigger event." There is need to improve awareness of emotional adjustment and their "triggers" amongst stroke survivors, carers and clinicians.